OPTIMALISASI PERAN KOMISI PENYIARAN INDONESIA DAERAH (KPID) DALAM MENGHADAPI TANTANGAN DI ERA DIGITAL - Dinny Wirawan Pratiwie; Nainuri Suhadi (Law Department, University of Widya Gama Mahakam Samarinda, 2025)
Background: The development of information and communication technology in the digital era has brought about quite significant changes in the world of broadcasting, both in terms of technical, regulatory and public consumption patterns of media. The presence of digital platforms such as streaming services, social media and other internet-based channels has challenged the existence of conventional broadcast media. This condition demands adaptation from broadcasting institutions and strengthening the role of institutions that supervise and regulate broadcasting, such as the Indonesian Broadcasting Commission (abbreviated as KPI). In East Kalimantan, the potential and challenges of digital broadcasting are increasingly visible with the increasing need for locally based information. However, if it is not balanced with clear regulations and synergy between stakeholders, local broadcasting could be threatened by digital content that is not in accordance with regional characteristics. Therefore, optimizing the role of Regional KPIs is very important to answer challenges in the digital era. Research Method: Research uses normative legal research methods, by examining applicable regulations or norms to find answers to the problems studied. The approach to this research is a statutory regulation approach. The legal materials used are primary legal materials in the form of statutory regulations. secondary legal materials in the form of journals, books and papers related to problems. Legal materials were collected using document studies and literature studies, while the data analysis technique used was qualitative analysis techniques. Findings: Increasing competition with digital platforms which come with all the ease of access and reach, has made KPID strive to increase synergy, especially with broadcasting institutions by accelerating the process of migrating analog broadcasts to digital in accordance with the mandate of the Job Creation Law as outlined in the Analog Switch Off (ASO) policy. With this policy, it requires adjustments to broadcasting regulations and institutional strengthening of KPI and KPID as independent broadcasting supervision institutions. Collaboration and coordination between KPID, broadcasting institutions and the government is increasingly strengthened, especially in terms of monitoring digital broadcast content. Conclusion: The Analog Switch Off policy is present in the context of digital information development, which influences aspects of broadcast supervision which is the task of KPID. Adjusting regulations and strengthening the Central KPI and KPID institutions is very important. Synergy between KPID, Regional Government and Broadcasting Institutions is an important point to optimize the role of broadcasting supervision. Synergy in terms of monitoring and developing content that is quality, educational and still represents local wisdom, as well as resolving disputes is the main key to facing broadcasting challenges in the digital era.